Towards Supporting Input-Output Relation within Harmony Search Strategy for T-Way Testing - Al-Sewari, Abdulrahman A.; Kamal Z., Zamli; Mohd Hafiz, Mohd Hassin (2013)
Over the last 10 years, many t-way testing strategies (where t represents the interaction strength) and their implementation tools have been applied in software testing. Much of existing work addresses the generation of test suite based on uniform and variable strength interactions. Although help-ful, existing strategies are not flexible enough to cater for specific parameter interactions based on input-output relationship. Addressing the aforemen-tioned issue, we are currently considering the support for Input Output rela-tion-based test suite as part of our existing strategy, HSS